Galvanic vestibular stimulation for the postural rehabilitation of HTLV-1-associated myelopathy - Silva, Tatiana Rocha; Labanca, Ludimila; Caporali, Júlia Fonseca de Morais; Tavares, Mauricio Campelo; Rausse, Nathália de Castro Botini; de Almeida, Maria Júlia Amaral Abranches; Martins, Maxmilliam de Souza; Amorim, Laura Fernandes; Sitibaldi, Léo Dantas; Gonçalves, Denise Utsch (Frontiers in Human Neuroscience, 2024)
IntroductionGalvanic vestibular stimulation (GVS) is a simple, safe, and noninvasive method of neurostimulation that can be used to improve body balance. Several central nervous system diseases cause alterations in body balance, including HTLV-1-associated myelopathy (HAM).ObjectiveTo test GVS as a balance rehabilitation strategy for HAM.MethodsThis study is a quasi-experimental clinical trial in which postural balance was compared before and after a GVS rehabilitation protocol applied to 20 patients with HAM, 12 women and 8 men, average age of 78 and 79 years, respectively. They were followed for nine months after the end of the GVS protocol, which consisted of one GVS session per week for 12 consecutive weeks. The GVS current intensity was progressively increased from 1.0 milliamperes (mA) to 3.5 mA until the third session and maintained at 3.5 mA until the 12th session. The electrical stimulation time progressively increased from 9 min in the first session to 18 min in the second session and maintained at 30 min from the third session onwards. Postural balance was assessed by Time up and go test (TUG), Berg balance scale (BBS) and posturography that were performed before the beginning of the intervention, during the intervention (6th week), at the end of the intervention (12th week) and after 9 months of follow-up without electrical stimulation.ResultsIn a blind comparison, in the 12th week of stimulation, improvement was observed in all the tests. In TUG, time in seconds changed from 28 before to 18 after GVS (p < 0,001). In BBS, the score changed from 29.00 before to 41.00 points after GVS. In posturography, the stability limit improved after the intervention (p < 0.05). However, after nine months without stimulation, the gain was lost for TUG, for BBS and for stability limit.ConclusionGVS was an effective method to improve postural instability of patients with HAM in the short term, but the gain in postural stability was not maintained in the long term. A device for home use may be an option for long-term use.